Percutaneous Fixation of Posterior Malleolar Fractures in Patients With Unstable Ankle Fractures Treated With a Fibular Intramedullary Nail: A Description of a Technique and Review of Outcomes. Issue 4 (April 2022) - Wordie, Sarah J.; Carter, Thomas H.; MacDonald, Deborah; Duckworth, Andrew D.; White, Timothy O.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To (1) describe the percutaneous technique used to reduce and fix a posterior malleolar fracture with anteroposterior screws in patients managed with a fibular intramedullary nail, (2) describe the selection of patients to whom this technique can be applied, and (3) report the clinical and patient reported outcome of this intervention. Design: Retrospective review. Setting: Academic orthopaedic trauma center. Patients: Thirty-two consecutive patients with a mean age of 65 years (range, 39–90) over a thirteen-year period identified from a prospective database. Intervention: Unstable ankle fractures managed surgically with a fibular nail and percutaneous fixation of the posterior malleolar component. Main Outcome Measurements: The primary short-term outcome was complications related to posterior malleolar fracture fixation. The primary mid-term outcome was the Olerud–Molander Ankle Score. Secondary outcomes included the Manchester–Oxford Foot Questionnaire, EuroQol-5D, health, pain, and satisfaction. Results: Thirty of the 32 (94%) posterior malleolar fractures united uneventfully. Postoperative loss of talar reduction occurred in 2 patients (6.3%), which in 1 patient (3.1%) eventually required a hindfoot nail arthrodesis. There were no soft-tissue complications related to the anteroposterior screws or the fibular nail fixation. At a mean follow-up of 3.7 years (range, 1–8), the median Olerud–Molander Ankle Score, Manchester–Oxford Foot Questionnaire, EuroQol-5D, health, pain, and satisfaction scores were 80.0, 23.4, 0.85, 80.0, 85.0, and 87.5, respectively. Conclusions: Percutaneous ankle fracture fixation with a fibular nail and posterior malleolar screws results in reliable fracture stabilization, good patient outcomes, and high treatment satisfaction. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.